The associations between water and sanitation and hookworm infection using cross-sectional data from Togo's national deworming program. - Julia M Baker; Victoria Trinies; Rachel N Bronzan; Ameyo M Dorkenoo; Joshua V Garn; Sêvi Sognikin; Matthew C Freeman (Public Library of Science (PLoS), 2018)
Sustainable control of soil-transmitted helminths requires a combination of chemotherapy treatment and environmental interventions, including access to safe drinking water, sufficient water for hygiene, use of clean sanitation facilities, and handwashing (WASH). We quantified associations between home-, school-, and community-level WASH characteristics and hookworm infection-both prevalence and eggs per gram of stool (intensity)-among Togolese school children in the context of community-based chemotherapy treatments administered in the country from 2010 through 2014.We analyzed data from two surveys conducted by the Togo Ministry of Health: a school-based survey of students aged 6-9 years across Togo conducted in 2009 and a follow-up survey in 2015, after four to five years of preventive chemotherapy. Data were available for 16,473 students attending 1,129 schools in 2009 and for 16,890 students from 1,126 schools in 2015. Between surveys, children in study schools received 0 to 8 rounds of deworming chemotherapy treatments. Few WASH conditions (only unimproved drinking water) were found to be significantly associated with the presence or absence of hookworms in an individual; however, quantitative eggs per gram of feces was associated with availability of unimproved drinking water, availability of improved drinking water either on or off school grounds, having a handwashing station with water available, and access to a sex-separate non-private or private latrine. The association between school WASH conditions and hookworm infection or burden often depended on the 2009 prevalence of infection, as more WASH characteristics were found to be significant predictors of infection among schools with high underlying endemicity of hookworm.Our findings emphasize the complex and often inconsistent or unpredictable relationship between WASH and hookworm. Specifically, we found that while preventive chemotherapy appeared to dramatically reduce hookworm infection, WASH was associated with infection intensity.